A novel automated alternating current biosusceptometry method to characterization of controlled-release magnetic floating tablets of metronidazole - Ferrari, Priscileila Colerato [UNESP]; Borella dos Santos Grossklauss, Dany Bruno [UNESP]; Alvarez, Matheus [UNESP]; Paixao, Fabiano Carlos [UNESP]; Andreis, Uilian [UNESP]; Crispim, Alexandre Giordano [UNESP]; Castro, Ana Doris de [UNESP]; Evangelista, Raul Cesar [UNESP]; Arruda Miranda, Jose Ricardo de [UNESP] (Informa Healthcare, 2014)
Context: Alternating Current Biosusceptometry is a magnetically method used to characterize drug delivery systems. This work presents a system composed by an automated ACB sensor to acquire magnetic images of floating tablets.Objective: The purpose of this study was to use an automated Alternating Current Biosusceptometry (ACB) to characterize magnetic floating tablets for controlled drug delivery.Materials and methods: Floating tablets were prepared with hydroxypropyl methylcellulose (HPMC) as hydrophilic gel material, sodium bicarbonate as gas-generating agent and ferrite as magnetic marker. ACB was used to characterize the floating lag time and the tablet hydration rate, by quantification of the magnetic images to magnetic area. Besides the buoyancy, the floating tablets were evaluated for weight uniformity, hardness, swelling and in vitro drug release.Results: The optimized tablets were prepared with equal amounts of HPMC and ferrite, and began to float within 4 min, maintaining the flotation during more than 24 h. The data of all physical parameters lied within the pharmacopeial limits. Drug release at 24 h was about 40%.Conclusions: The ACB results showed that this study provided a new approach for in vitro investigation of controlled-release dosage forms. Moreover, using automated ACB will also be possible to test these parameters in humans allowing to establish an in vitro/in vivo correlation (IVIVC).
Keywords: Biosusceptometry; controlled drug release; floating tablets; magnetic marker; swelling